Concluding Comment: Moral Responsibility and Civic Responsiveness: Spectacles of Suffering on Digital Media - Chouliaraki, Lilie (Javnost-The Public, 2016)
This special section brings together four original contributions on an emerging problematic around moral spectatorship—the problematic of when, how and to which effect citizens respond to mediated suffering on digital platforms. In my brief commentary, I draw on insights from these four contributions to reflect on two themes that emerge as central to this problematic: the conditions of possibility for digital moral spectatorship and the resources of reflexivity that constitute digital spectatorship as online action.